Prevalência e fatores genéticos associados à fluorose dentária em um município de grande porte do sul do Brasil - Dalledone, Mariana (2018)
Adding fluoride to the supply water is the most effective method to prevent tooth decay. Large populations worldwide are benefited by this method, relatively simple and inexpensive, however, despite excellent results in preventing dental caries disease, on the other hand, the prevalence of dental fluorosis has greatly increased. This research aimed to investigate the prevalence of dental fluorosis in the population of Curitiba between the years 2006 and 2016, as well as to analyze if genetic polymorphisms are associated with this condition. In order to make the sample representative of the whole city, 679 and 934 children of 12 years old were examined in 2006 and 2016 respectively. Clinical examinations were performed at school and the modified Dean index was used to classify dental fluorosis (DF). In the year 2006, biological material was collected of 538 children to evaluate whether the genetic polymorphisms in the estrogen receptor (ESR1, ESR2, ESRRB) gene, are associated with this condition. The results showed that the prevalence of DF in the studied population decreased from 27.7% to 17.2%. Cases of mild and severe fluorosis decreased and there was no difference between the various sanitary districts of the city. . The phenotypic distribution for rs12154178 polymorphism was associated with dental fluorosis (p = 0.037). The analysis of the dominant model (AA + AC vs. CC) showed that CC is a protective factor for FD (p = 0.038; OR = 0.51, 0.27- 0.97 CI95%). The results obtained suggest that the cases of dental fluorosis in the city of Curitiba between the years 2006 and 2016 probably is not only associated with the fluoridation of water supply since there was genetic evidence that the rs12154178 polymorphism in ERS1 in the dominant model, is associated with the risk of dental fluorosis.